Implementasi Putusan Hakim dalam Penjatuhan Pidana Terhadap Pelaku Tindak Pidana Korupsi secara Bersama-Sama pada BUMD Tanggamus : Studi Putusan Nomor: 24/Pid.Sus-Tpk/2025/PN.Tjk - Heriyanti, Rosmeli; Hartono, Bambang; Ramadan, Suta (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The criminal act of corruption committed collectively within the Regionally Owned Enterprises (BUMD) is a form of crime that has a serious impact on regional finances and public trust in the administration of government. This study aims to analyze the implementation of the judge's decision in sentencing perpetrators of corruption committed collectively at the Tanggamus BUMD as stated in Decision Number : 24/Pid.Sus-Tpk/2025/PN.Tjk. The research method used is normative legal research with a statutory approach and a case approach, through a study of court decisions, provisions of criminal law on corruption, and relevant legal doctrines. The results of the study indicate that the panel of judges has applied the provisions of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. This decision demonstrates the judiciary's efforts in upholding the principles of justice, legal certainty, and benefit, while also serving as a deterrent instrument against criminal acts of corruption committed collectively the BUMD.